2015
DOI: 10.3917/spub.150.0119
|View full text |Cite
|
Sign up to set email alerts
|

Les nouvelles formes d’organisations de soins de santé primaires (OSSP) sont-elles associées à une meilleure expérience de soins chez les patients atteints de maladies chroniques au Québec ?

Abstract: La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éditeur, en dehors des cas prévus par la législation en vigueur en France. Il est précisé que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a study on the experience of care of patients with chronic illnesses, conducted using the same data set, the authors concluded that all experience of care indicators were high for this type of patient, except accessibility. 33 By isolating the effect of registered nurses’ systematic follow-up on experience of care, our study has shown that, in PHCOs where registered nurses perform systematic follow-up, accessibility is enhanced.…”
Section: Discussionmentioning
confidence: 81%
“…In a study on the experience of care of patients with chronic illnesses, conducted using the same data set, the authors concluded that all experience of care indicators were high for this type of patient, except accessibility. 33 By isolating the effect of registered nurses’ systematic follow-up on experience of care, our study has shown that, in PHCOs where registered nurses perform systematic follow-up, accessibility is enhanced.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have demonstrated the impact of PHC services organization on patients' experience of care and other aspects of health services utilization [ 24 – 28 ]. Commonwealth Fund data compiled from several countries show considerable variation in patients' reported experience of care in terms of accessibility, continuity, comprehensiveness, care coordination, and chronic illness management [ 29 ].…”
Section: Introductionmentioning
confidence: 99%